Building an Integrated Foreclosure Enforcement System in the Post-Auction Eviction Execution of Mortgage Rights - Michelle Tiffani; Mochamad Rizqi Zia Ulhaq; Dewi Sulistianingsih; Pujiono Pujiono (Universitas Negeri Semarang, 2026)
The post-auction eviction execution of Mortgage Rights objects constitutes a crucial stage in the enforcement of security rights because it determines the effectiveness of the auction winner’s physical possession of the property. However, the Indonesian civil procedural law system still separates auction proceedings and eviction execution into two distinct processes, resulting in procedural uncertainty, additional litigation, and obstacles to enforcement implementation. This study aims to analyze the normative weaknesses and practical problems in the implementation of post-auction eviction execution and to formulate a reform model through the concept of an Integrated Foreclosure Enforcement System. This research employs normative legal research methods using statutory, conceptual, case, and comparative approaches. Legal materials are analyzed qualitatively through systematic, historical, and teleological interpretation. The findings indicate that the use of HIR and RBg as the legal basis for eviction execution is no longer compatible with the needs of modern foreclosure enforcement because they fail to integrate auction proceedings, transfer of rights, and physical possession of the object into a unified enforcement mechanism. Furthermore, weak institutional coordination, the absence of limitations on procedural abuse, and social resistance also contribute to the ineffectiveness of post-auction eviction execution. Based on a comparative analysis with the Netherlands and South Korea, this study proposes the concept of an Integrated Foreclosure Enforcement System emphasizing procedural integration, strengthening enforcement institutions, digitalization of execution administration, limitations on obstructive lawsuits and derden verzet, and a human-rights-based enforcement approach. Such reforms are necessary to establish a foreclosure enforcement system that is effective, certain, equitable, and supportive of the modernization of Indonesian civil procedural law.